(untitled) (UNIZIK Journal of Educational Management and Policy, 2025)
This study explores the effectiveness of Artificial Intelligence (AI) in enhancing school security management within public secondary schools in Anambra State, Nigeria. With increasing incidents of theft, vandalism, unauthorized access, and student unrest, traditional security measures have proven insufficient in safeguarding educational environments. AI technologies—such as motion-detection cameras, facial recognition systems, predictive analytics, and automated alert mechanisms—offer innovative solutions that improve surveillance, response times, and overall safety. Quantitative findings from existing literature indicate significant reductions in security breaches and faster incident resolution following AI implementation. Qualitative insights reveal increased stakeholder confidence in safety protocols and more data-informed decision-making among school administrators. Despite these benefits, challenges persist. Infrastructure limitations, financial constraints, lack of technical expertise, and ethical concerns around data privacy hinder widespread adoption. The study recommends piloting low-cost, scalable AI tools, strengthening human capacity through training, and integrating community-based security efforts. Establishing robust data governance frameworks and legal safeguards is essential to ensure responsible use and stakeholder trust. Strategic partnerships with technology providers, government agencies, and development organizations can offset costs and support sustainable implementation. The conclusions emphasizes AI’s potential to revolutionize school security management in Anambra State. When deployed thoughtfully and contextually, AI can create safer learning environments, support educational continuity, and prepare schools for future challenges. This study contributes to the growing discourse on technology-driven education reform and offers practical recommendations for policymakers, educators, and stakeholders seeking to enhance school safety through intelligent systems.